Spent coffee ground-based materials evaluated by methylene blue removal - Araya-Sibaja, Andrea Mariela; Quesada-Soto, Tamara; Vega-Baudrit, José Roberto; Navarro-Hoyos, Mirtha; Valverde-Cerdas, Johnny; Romero-Esquivel, Luis Guillermo (Processes 2025, 2025)
Spent coffee grounds (SCG) are produced in large quantities during coffee brewing, contributing to environmental concerns. Additionally, cationic dyes from textile, paper, and leather wastewater pose a major pollution issue. This study explores SCG as an adsorbent for methylene blue (MB) dye. A novel comparison of SCG cleaning methods with warm water, accelerated solvent extraction (ASE), supercritical fluid extraction (SFE), and ultrasound-induced cavitation (US) is presented. In addition, the chemical modifications of SCG using acetylation, acid (HNO3), and base (KOH) treatment that have not been reported before are presented. ATR-FTIR confirmed the inclusion of functional groups, for example, the nitro group in SCG treated with HNO3, and an increase in carboxylic groups in the samples treated with KOH and HNO3. SEM analysis revealed a consistent porous texture across samples, with SCG-SFE, SCG-US, and SCG-HNO3 showing smaller pores, and SCG-ASE displaying elongated cavities. Adsorption isotherm tests followed the Freundlich and Langmuir models, indicating favorable adsorption. The Langmuir maximum adsorption capacity (qmax) varied among cleaning methods from 65.69 mg/g (warm water) to 93.32 mg/g (SFE). In contrast, in base- and acid-treated SCG, a three- to four-fold increase in adsorption capacity was observed, with qmax values of 171.60 mg/g and 270.64 mg/g, respectively. These findings demonstrate that SCG washed with warm water and chemically treated achieves adsorption capacities comparable to other biosorbents reported in the literature. Therefore, SCG represents a promising, low-cost, and sustainable material for removing cationic dyes from wastewater, contributing to waste valorization and environmental protection.
Artículo. Instituto Tecnológico de Costa Rica (ITCR). Escuela de Química. Centro de Investigación en Protección Ambiental (CIPA), Laboratorio Nacional de Nanotecnología LANOTEC-CeNAT-CONARE, Universidad Técnica Nacional (UTN), Universidad de Costa Rica (UCR). Departamento de Química. Bioactividad para el Desarrollo Sostenible (BIODESS), Georgetown University. Chemistry Department, 2025
Keywords: Materiales molidos de café; Compuestos químicos; Azul de metileno; Capacidad de adsorción; Colorantes catiónicos; Agua residual; Economía circular; Colorantes orgánicos solubles; Cavitación; Protección del medio ambiente; Research Subject Categories::TECHNOLOGY::Chemical engineering; Research Subject Categories::TECHNOLOGY::Other technology::Environmental engineering